Acquired ROS1 fusion and iruplinalkib response in advanced NSCLC after multiple lines of systematic therapy: a case report - Liu, Jiarui; Jiao, Zhichao; Zhou, Jun; Yuan, Yuan; Li, Qiguang; Zhou, Wei; Zhang, Shuai; Yang, Shuping (Frontiers in Oncology, 2025)
This is the first report of a patient with lung cancer whose primary focus was the upper lobe of the left lung combined with multiple metastases in both lungs, initially diagnosed as a non-driver gene mutation, who subsequently developed SDC4-ROS1 fusion after multiple lines of systemic therapy. When diagnosis, a needle biopsy of the primary focus revealed no driver gene mutation and low PD-L1 expression (TPS < 1%, CPS 3). From November 2022 to December 2023, the patient received sequential chemotherapy-based systemic therapy including anti-angiogenesis treatment, concurrent chemoradiation and combined immunotherapy as determined by the clinician based on the initial evaluation. In December 2023, a needle biopsy of a metastasis in the left lower lobe of the lung showed a positive SDC4-ROS1 fusion. Subsequent treatment with the oral ALK TKI iruplinalkib was initiated based on the patient’s preference, which exhibited a promising response over the next 2 months.